Stereotactic Thermal Ablation of Liver Tumors: 3D Planning, Multiple Needle Approach, and Intraprocedural Image Fusion Are the Key to Success—A Narrative Review - Gregor Laimer; Peter Schullian; Reto Bale (Biology, 2021)
Thermal ablation is an emerging, potentially curative approach in treating primary and metastatic liver cancer. Different technologies are available, with radiofrequency ablation (RFA) and microwave ablation (MWA) being the most widely used. Regardless of the technique, destruction of the entire tumor, including an adequate safety margin, is key. In conventional single-probe US- or CT-guided thermal ablation, the creation of such large necrosis zones is often hampered by technical limitations, especially for large tumors (i.e., >2–3 cm). These limitations have been overcome by stereotactic RFA (SRFA): a multiple needle approach with 3D treatment planning and precise stereotactic needle placement combined with intraprocedural image fusion of pre- and post-interventional CT scans for verification of treatment success. With these sophisticated tools and advanced techniques, the spectrum of locally curable liver malignancies can be dramatically increased. Thus, we strongly believe that stereotactic thermal ablation can become a cornerstone in the treatment of liver malignancies, as it offers all the benefits of a minimally invasive method while providing oncological outcomes comparable to surgery. This article provides an overview of current stereotactic techniques for thermal ablation, summarizes the available clinical evidence for this approach, and discusses its advantages.